Effectiveness of intramuscular neostigmine to accelerate bladder emptying after spinal anesthesia - Senapathi TGA; Wiryana M; Subagiartha IM; Suarjaya IPP; Widnyana IMG; Sutawan IBKJ; Jaya AAGPS; Thewidya A (Dove Medical Press, 2018)
Tjokorda Gde Agung Senapathi, Made Wiryana, I Made Subagiartha, I Putu Pramana Suarjaya, I Made Gede Widnyana, Ida Bagus Krisna Jaya Sutawan, A A Gde Putra Semara Jaya, Andri Thewidya Department of Anesthesiology and Intensive Care, Sanglah Hospital, Faculty of Medicine, Udayana University, Denpasar, Bali, Indonesia Purpose: Postoperative urinary retention (POUR) is one of the most common complications following spinal anesthesia. Spinal anesthesia may influence urinary bladder function due to interruption of the micturition reflex. Urinary catheterization is the standard treatment of POUR. Urinary catheter insertion is an invasive procedure, which is associated with catheter-related infections, urethral trauma, and patient discomfort. The purpose of this study was to determine the effectiveness of intramuscular (IM) neostigmine to accelerate bladder emptying after spinal anesthesia. Patients and methods: A total of 36 patients undergoing lower abdominal (except for pelvic, urologic, anorectal, and hernia surgery) and lower extremity surgery under spinal anesthesia were divided into two groups randomly (n=18), to either neostigmine (N) group or control (C) group. Neostigmine 0.5 mg (N group) or NaCl 0.9% (C group) was administered intramuscularly when Bromage score 0 and sensory level sacral two have been achieved. The time to first voiding after IM injection and the time to first voiding after spinal anesthesia were measured. Results: The time to first voiding after IM injection was significantly faster (P≤0.05) in the N group than that in the C group, with median time as 40 minutes (20–70 minutes) and 75 minutes (55–135 minutes), respectively. Time to first voiding after spinal anesthesia was also significantly faster (P≤0.05) in the N group than that in the C group (mean of 280.8±66.6 minutes and 364.2±77.3 minutes, respectively). Conclusion: IM neostigmine effectively accelerates bladder emptying after spinal anesthesia. Keywords: neostigmine, postoperative urinary retention, bladder emptying, spinal anesthesia, anticholinesterase, neuraxial anesthesia